Sleep patterns modify the association of 25(OH)D with poor cardiovascular health in pregnant women - Yin, Wan-jun; Yu, Li-jun; Wang, Peng; Tao, Rui-xue; Jiang, Xiao-min; Zhang, Ying; Zhu, Dao-min; Zhu, Peng (Frontiers in Nutrition, 2022)
Background: The association of vitamin D status and supplementation with gestational cardiovascular health (CVH) is inconsistent in previous studies. Emerging evidence shows that sleep behaviors are related to vitamin D metabolism. However, no studies evaluate the interaction of vitamin D and sleep behaviors on gestational CVH. Objective: We aimed to estimate the relation between 25-hydroxyvitamin D [25(OH)D] concentrations and gestational CVH, and whether such relation was modified by sleep behaviors. Methods: The study was based on a multicenter birth cohort study that included 9209 pregnant women at 16 to 23 gestational weeks. 25(OH)D concentrations were measured from collected blood. A healthy sleep score consisted of major sleep behaviors including duration, chronotype, insomnia, snoring, and excessive daytime sleepiness, defined by sleep patterns. Data of gestational CVH was based on four “clinical” CVH metrics, including body mass index, blood pressure, total cholesterol, and the gestational diabetes mellitus diagnosis, obtained from the hospitals at 24 to 28 gestational weeks. Results: The proportion of women with poor CVH was 25.0%. The relative risk (RR) (95%CI) of poor CVH was 0.67 (0.58–0.76) in women with 25(OH)D  50 nmol/L after multivariate adjustments. Lower 25(OH)D concentrations were significantly associated with poor CVH. Such association was also evident in subgroups subgroup analysis. We found a significant interaction of 25(OH)D (P for interaction =0.004) with sleep patterns on the risk of poor CVH. 25(OH)D concentrations were inversely associated with the risk of poor CVH in a dose-response fashion among healthy or intermediate sleep, not among poor sleep. 25(OH)D concentrations were lower and the risk of poor CVH was higher in pregnant women with poor sleep patterns (P < 0.05). Conclusions: Our study suggests that sleep patterns modify the association of 25(OH)D concentrations with the CVH among pregnant women.